MoS2 quantum dot decorated RGO: a designed electrocatalyst with high active site density for the hydrogen evolution reaction. Issue 43 (30th September 2015) - Li, Feng; Li, Jing; Cao, Zhuo; Lin, Xiaoqing; Li, Xinzhe; Fang, Yiyun; An, Xincai; Fu, Yan; Jin, Jun; Li, Rong
Abstract : In the present work, MoS2 quantum dots (MoS2 QDs) decorated on reduced graphene oxide (RGO) as highly effective electrocatalysts were synthesized by a facile sonication method for the hydrogen evolution reaction (HER). Abstract : Active, stable and cost-effective electrocatalysts are the key to water splitting for hydrogen production through electrolysis. In this work, we report MoS2 quantum dots (MoS2 QDs) decorated on reduced graphene oxide (RGO) synthesized by a facile sonication method as highly effective electrocatalysts for the hydrogen evolution reaction (HER). Compared with MoS2 sheets, the zero-dimensional MoS2 QDs have a defect-rich structure rendering these quantum dots with plentiful active sites, which can further enhance the catalytic activity by a synergistic effect with RGO. Electrochemical experiments demonstrated that the catalyst exhibited large cathode currents (a small overpotential of 64 mV for 10 mA cm −2 current density) and a Tafel slope as small as 63 mV per decade, achieving high stability simultaneously. This work opens up possibilities for preparing non-noble metal electrocatalysts while achieving high HER performance similar to commercial Pt catalysts (Pt/C).